Invest In India–The Foreign Direct Investment Scenario - B, Kamaladevi (Information Management and Business Review, 2011)
Invest in India is an initiative to market India as an investment destination all over the globe, to provide a networking platform to the Indian businesses at a global level and to provide information to the international investors about investment opportunities in India. It is the policy of the Government of India to attract and promote productive Foreign Direct Investment (FDI) from non-residents in activities which significantly contribute to industrialization and socio-economic development. FDI supplements the domestic capital and technology. This paper firstly speaks about the FDI culture in India, secondly, reviews economic reforms in India and global response to India’s reforms, the next level discusses the policy issues that would address India’s relative lack of success in attracting FDI and the ‘Expanding Opportunities for Global Retailers’ with reference to the retail sector. The last part reveals the key recommendations towards attracting Diaspora FDI. Based on the objective analysis, the key recommendations towards attracting FDI are revealed like allow 100 % FDI in retail and Small & Medium Enterprises (SME), develop a strategic vision for FDI with focus on latest technology, reduce the transaction costs & improve the infrastructure, international and domestic entrepreneurship, decentralize the administration process, reduce overly bureaucratic FDI facilities, private public partnership with private sector taking the lead, Indian professionals placed in key decision making positions, creative joint ventures and partnership to tap entrepreneurship and fix the policies to convert remittances into investment & create venture capital.